{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# soln7 - EECS 451 SOLUTIONS TO PROBLEM SET#7 1a Reverse the...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: EECS 451 SOLUTIONS TO PROBLEM SET #7 1a. Reverse the second sequence: { 4 , 3 , 2 , 2 } → { 2 , 2 , 3 , 4 } , repeat the cycle, and shift: y(0): { 1 , 2 , 3 , 1 , 1 , 2 , 3 , 1 } { 4 , 2 , 2 , 3 , 4 , 2 , 2 , 3 } → (1)(4) + (2)(2) + (3)(2) + (1)(3) = 17. y(1): { 1 , 2 , 3 , 1 , 1 , 2 , 3 , 1 } { 3 , 4 , 2 , 2 , 3 , 4 , 2 , 2 } → (1)(3) + (2)(4) + (3)(2) + (1)(2) = 19. y(2): { 1 , 2 , 3 , 1 , 1 , 2 , 3 , 1 } { 2 , 3 , 4 , 2 , 2 , 3 , 4 , 2 } → (1)(2) + (2)(3) + (3)(4) + (1)(2) = 22. y(3): { 1 , 2 , 3 , 1 , 1 , 2 , 3 , 1 } { 2 , 2 , 3 , 4 , 2 , 2 , 3 , 4 } → (1)(2) + (2)(2) + (3)(3) + (1)(4) = 19 . { 17 , 19 , 22 , 19 } . 1b. X 1 (0) = 1 + 2 + 3 + 1 = 07 . X 1 (1) = 1 + 2(- j ) + 3(- 1) + 1( j ) =- 2- j . X 1 (2) = 1- 2 + 3- 1 = 01 . X 1 (3) = 1 + 2( j ) + 3(- 1) + 1(- j ) =- 2 + j . X 2 (0) = 4 + 3 + 2 + 2 = 11 . X 2 (1) = 4 + 3(- j ) + 2(- 1) + 2( j ) = +2- j . X 2 (2) = 4- 3 + 2- 2 = 01 . X 2 (3) = 4 + 3( j ) + 2(- 1) + 2(- j ) = +2 + j ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 2

soln7 - EECS 451 SOLUTIONS TO PROBLEM SET#7 1a Reverse the...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online